Construction of systems of frequency impedance metering of biological tissues using “Arduino” platforms - Bykh, A.I.; Kosin, U.I.; Leonidov, V.I.; Kravtsov, A.V.; Bobnev, R.A. (Radiotekhnika, 2018)
The electrical properties of biological tissue of vegetable origin are investigated, an algorithm for the functioning of the system for calculating the viability factor built on the basis of the “Arduino” platform is considered.